Respuesta :
(w + 5) - 5 = 2w + 5
w + 5 - 5 = 2w + 5 (remove bracket cuz unneeded)
w = 2w + 5 (5 and -5 cancel on left side)
-w = 5 (subtract 2w on both sides)
w = -5 (convert -w to w)
Therefore w = -5
Proof:
(w + 5) - 5 = 2w + 5
(-5 + 5) - 5 = 2(-5) + 5
0 - 5 = -10 + 5
-5 = -5
Hope I helped :P
w + 5 - 5 = 2w + 5 (remove bracket cuz unneeded)
w = 2w + 5 (5 and -5 cancel on left side)
-w = 5 (subtract 2w on both sides)
w = -5 (convert -w to w)
Therefore w = -5
Proof:
(w + 5) - 5 = 2w + 5
(-5 + 5) - 5 = 2(-5) + 5
0 - 5 = -10 + 5
-5 = -5
Hope I helped :P